Prosthesis-user-in-the-loop: User-centered design parameters and visual simulation - Christ, O.; Wojtusch, J.; Wolff, K.; Vogt, J.; Von Stryk, O.; Rinderknecht, S.; Beckerle, Philipp (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2012)
After an amputation, processes of change in the body image as well as a change in body scheme have direct influences on the quality of living in every patient. Within this paper, a paradigm of experimental induced body illusion (the Rubber Hand Illusion, RHI) is integrated in a prosthetic hardware simulator concept. This concept combines biodynamical and visual feedback to enhance the quality of rehabilitation and to integrate patients' needs into the development of prostheses aiming on user-centered solutions. Therefore, user-centered design parameters are deducted. Furthermore, the basic concept of the visual simulation is presented and a possibility for its implementation is given. Finally, issues and conclusions for future work are described. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-09-24